University library buildings:"Foundations and Standards" (Damascus University Journal of arts and humanities sciences, 2022)
The university libraries represented the heart of the university, because it is contribute with improvement most of the university purposes, at the educational and science researches, serving the local society.The library aimed to activate these purposes by applying services to all information requested at the comfort and calm situation. From this point, this research coming to definite the suitability of the university building, and its equipments, furniture's, to special basic standards in libraries building, to apply comfort situation, and more efficiency in applying these services.
Keywords: university libraries; Library buildings